The difficulties encountered in conversion from classic pancreaticoduodenectomy to total laparoscopic pancreaticoduodenectomy - Muharrem Battal; Ahmet Yilmaz; Gokmen Ozturk; Oguzhan Karatepe (Journal of Minimal Access Surgery, 2016)
Background: Recently, total laparoscopic pancreatectomy has been performed at many centres as an alternative to open surgery. In this study, we aimed to present the difficulties that we have encountered in converting from classic open pancreaticoduodenectomy to total laparoscopic pancreatectomy. Materials and Methods: Between December 2012 and January 2014, we had 100 open pancreaticoduodenectomies. Subsequently, we tried to perform total laparoscopic pancreaticoduodenectomy (TLPD) in 22 patients. In 17 of these 22 patients, we carried out the total laparoscopic procedure. We analysed the difficulties that we encountered converting to TLPD in three parts: Preoperative, operative and postoperative. Preoperative difficulties involved patient selection, preparation of operative instruments, and planning the operation. Operative difficulties involved the position of the trocars, dissection, and reconstruction problems. The postoperative difficulty involved follow-up of the patient. Results: According to our experiences, the most important problem is the proper selection of patients. Contrary to our previous thoughts, older patients who were in better condition were comparatively more appropriate candidates than younger patients. This is because the younger patients have generally soft pancreatic texture, which complicates the reconstruction. The main operative problems are trocar positions and maintaining the appropriate position of the camera, which requires continuous changes in its angles during the operation. However, postoperative follow-up is not very different from the classic procedure. Conclusion: TLPD is a suitable procedure under appropriate conditions.